Manganese and copper contents in musts of 'Isabel' and 'Concord' grapes - Miele, Alberto (2014)
The Mn and Cu contents in musts of 'Isabel' and 'Concord' grapes have been determined. The samples were collected in 1981 from 61 vineyards of each one of these two cultivars. The results have shown that the Cu content was higher in the must of 'Isabel' (3.33 mg/l) than in 'Concord' (1.42 mg/l). However, the contrary occurred with the Mn, as the content of this element was higher in 'Concord' (2.32 mg/l) than in 'Isabel' (0.69 mg/l). The concentrations of Mn and Cu were related to the fungicide spray programmes adopted by the growers. But the highest value of Mn in 'Concord' musts seems to be a varietal characteristic.